Thoracic endovascular aortic repair under venoarterial extracorporeal membrane oxygenation for acute aortic dissection patients: a case report - Zhu, Leilei; Dong, Pingping; Du, Liwen; Xun, Kai; Liu, Peng; Lu, Xiaozhen; Shi, Yongwei (Frontiers in Cardiovascular Medicine, 2023)
Background: For most patients with type A aortic dissection, open repair and replacement of the diseased aorta is still the standard treatment. In endovascular treatment alone, it is difficult to ensure adequate blood supply to the brain while covering the dissection with a stent.Case presentation: A 71-year-old male patient with type A aortic dissection presented at a recent follow-up examination after having undergone TEVAR plus left subclavian artery chimney stent reconstruction for descending aortic dissection 5 years earlier. Preoperative CTA, CTP and TCD showed an intact cerebral arterial ring and good collateral circulation. We successfully performed an endovascular repair of the thoracic aorta with V-A ECMO to protect the craniocerebral blood supply, greatly increase the safety of the operation, and ensure a good prognosis. Conclusion: TEVAR under V-A ECMO protection is beneficial for patients with TAAD because of its minimal trauma, rapid recovery, few complications and low mortality.